Protocol to study chloride regulation in cultured mouse cortical neurons using electrophysiology - Vineeth A. Raveendran; Jessica C. Pressey; Melanie A. Woodin (STAR Protocols)
Summary: Inhibitory synaptic transmission mediated by the neurotransmitter γ-aminobutyric acid (GABA) is dependent on the concentration of chloride ions (Cl−) in neurons, which can be assessed by making patch-clamp recordings of the reversal potential for GABA (EGABA). Here, we present a protocol to study the regulation of cation-chloride cotransporters and the strength of synaptic inhibition in cultured mouse cortical neurons using electrophysiology. We describe steps for culturing neurons isolated from postnatal pups and electrophysiological measurement of EGABA.For complete details on the use and execution of this protocol, please refer to Raveendran et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.